2016
DOI: 10.1093/femsec/fiw107
|View full text |Cite
|
Sign up to set email alerts
|

Role of secondary metabolites in the interaction betweenPseudomonas fluorescensand soil microorganisms under iron-limited conditions

Abstract: Microorganisms can be versatile in their interactions with each other, being variously beneficial, neutral or antagonistic in their effect. Although this versatility has been observed among many microorganisms and in many environments, little is known regarding the mechanisms leading to these changes in behavior. In the present work, we analyzed the mechanism by which the soil bacterium Pseudomonas fluorescens BBc6R8 shifts from stimulating the growth of the ectomycorrhizal fungus Laccaria bicolor S238N to kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…When developing new biological preparations, antagonistic interactions between different microorganisms are adopted as well as antagonistic reactions between produced metabolites and the phytopathogens. The antagonistic bacteria are among others: Pseudomonas fluorescens, P. putida, P. malophilia, Agrobacterium radiobacter, Bacillus subtilis, B. cereus, B. amyloliquefaciens, B. mycoides, B. brevis, Serratia odorifera, Pantoea agglomerans [6][7][8][9][10]. Their mode of plant's health improvement is mainly based on the pathogen's growth inhibition and an induction of plant's resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When developing new biological preparations, antagonistic interactions between different microorganisms are adopted as well as antagonistic reactions between produced metabolites and the phytopathogens. The antagonistic bacteria are among others: Pseudomonas fluorescens, P. putida, P. malophilia, Agrobacterium radiobacter, Bacillus subtilis, B. cereus, B. amyloliquefaciens, B. mycoides, B. brevis, Serratia odorifera, Pantoea agglomerans [6][7][8][9][10]. Their mode of plant's health improvement is mainly based on the pathogen's growth inhibition and an induction of plant's resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Their mode of plant's health improvement is mainly based on the pathogen's growth inhibition and an induction of plant's resistance. However, there are a few mechanisms employed in their antagonistic activity against pathogens, which include: a competition for living space and nutrients, mycoparasite, production of antifungal compounds including antibiotics and toxins, induction of plant's resistance ISR (Induced Systemic Resistance), production of volatile compounds inhibiting pathogens' growth which may play an important role in a biocontrol process [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Siderophores modulate the availability of iron, which indirectly stimulates the biosynthesis of other antimicrobial compounds (Duffy and Défago ). Maldonado‐González et al () reported that pyoverdine was not a key factor for biocontrol ability of P. fluorescens PICF7, whereas Deveau et al () showed that pyoverdine was responsible for antagonism against fungus Laccaria bicolor S238N and actinomycete Streptomyces ambofaciens ATCC 23877 under iron‐limited conditions. Several pyoverdine‐related genes contributed to the swarming motility of Pseudomonas aerudinosa PA14 (Strehmel et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MALDI mass spectrometry of P. aeruginosa treated with macrolide antibiotic azithromycin demonstrated the inability of azithromycin to inhibit cell-to-cell signaling in pathogenic strains of P. aeruginosa (Phelan et al 2015). Also, using MALDI-IMS, a significant study determined the siderophore pyochelin as the main antagonizing metabolite of P. fluorescens BBc6R8 against ectomycorrhizal fungus Laccaria bicolor S238N (Deveau et al 2016). The integration of MALDI-IMS with LC-MS/MS techniques has successfully unveiled the potential adaptability of pseudomonads in response to challenging environmental conditions.…”
Section: New Techniques and Tools Helped To Understand Complex Chemicmentioning
confidence: 99%